Impact of Interstitial Lung Disease Classification on the Development of Acute Exacerbation of Interstitial Lung Disease and Prognosis in Patients with Stage III Non-Small-Cell Lung Cancer and Interstitial Lung Disease Treated With Chemoradiotherapy - Kobayashi, Haruki (J Cancer, 2018)
Introduction: Data on the efficacy and risk of curative-intent chemoradiotherapy in patients with inoperable stage III non-small-cell lung cancer (NSCLC) and interstitial lung disease (ILD) are limited. The aim of this study was to explore the impact of ILD classification on acute exacerbation (AE) of ILD and prognosis in patients with stage III NSCLC and ILD treated with chemoradiotherapy. Materials and methods: We retrospectively reviewed the medical records of patients with stage III NSCLC and ILD treated with curative-intent chemoradiotherapy as the first-line treatment at the Shizuoka Cancer Center between June 2009 and May 2014. Results: Of 37 patients, 17 (46%) developed AE of ILD worse than grade 3 within 1 year after the last irradiation. In univariate analysis, the incidence rate of AE of ILD was lower in patients with a non-usual interstitial pneumonia (UIP) pattern than in those with a UIP pattern. Multivariate analysis showed that ILD classification was significantly associated with the incidence of AE of ILD. The median overall survival (OS) durations in patients with a non-UIP pattern and a UIP pattern were 16.5 and 9.3 months, respectively. In univariate analysis, patients with a non-UIP pattern showed better survival. Multivariate analysis showed that ILD classification was a significant independent prognostic factor. Conclusion: The incidence of AE of ILD was high in patients with stage III NSCLC and ILD treated with chemoradiotherapy as the first-line treatment. However, diagnosis of a non-UIP pattern could predict lower risk of AE of ILD and longer OS durations.